2019
DOI: 10.22456/1982-8918.86965
|View full text |Cite
|
Sign up to set email alerts
|

Precários No Trabalho E No Lazer: Um Estudo Sobre Os Professores Da Rede Estadual Paulista

Abstract: Esta pesquisa teve como objetivo geral investigar as manifestações do fenômeno lazer entre trabalhadores docentes que integram o quadro funcional da Secretaria da Educação do Estado de São Paulo. Ao mesmo tempo, como objetivo específico, buscou identificar de que forma as oscilações relativas às distintas relações de trabalho, sobretudo a evidente condição de precariedade, influenciam o lazer da categoria em questão. É um estudo de caso, realizado com 29 trabalhadores docentes que atuam em escolas dessa rede d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…Representa mais uma faceta de atividades que devem ser desempenhadas pelos professores. Os docentes sentem dificuldades de utilizar ao mesmo tempo materiais didáticos e tecnologias como computador e microfone (Oliveira, Gonçalves, Melo, Fardin, & Mill, 2002;Silva & Claro, 2007;Seno, 2007;Konrath, Tarouco, & Behar, 2009;Ribeiro, 2011;Carvalho, 2011;Mandernach, Hudson, & Wise, 2013;Yildiz & Selim, 2015;Duarte & Massuda, 2019;Silvestre & Amaral, 2019).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Representa mais uma faceta de atividades que devem ser desempenhadas pelos professores. Os docentes sentem dificuldades de utilizar ao mesmo tempo materiais didáticos e tecnologias como computador e microfone (Oliveira, Gonçalves, Melo, Fardin, & Mill, 2002;Silva & Claro, 2007;Seno, 2007;Konrath, Tarouco, & Behar, 2009;Ribeiro, 2011;Carvalho, 2011;Mandernach, Hudson, & Wise, 2013;Yildiz & Selim, 2015;Duarte & Massuda, 2019;Silvestre & Amaral, 2019).…”
Section: Resultsunclassified
“…É necessário que o professor desenvolva novas competências porque o teletrabalho exige redimensionamento da sua prática docente, adequando-se ao novo ambiente comunicacional e ao novo espaço de sociabilidade, organização, informação e conhecimentos próprios da cibercultura. É necessário enfatizar a importância da capacitação docente, a partir da premissa de que o professor é um dos elementos principais no processo de ensino e aprendizagem a distância (Silva & Claro, 2007;Seno, 2007;Konrath, Tarouco, & Behar, 2009;Ribeiro, 2011;Carvalho, 2011;Mandernach, Hudson, & Wise, 2013;Yildiz & Selim, 2015;Duarte & Massuda, 2019;Silvestre & Amaral, 2019).…”
Section: Resultsunclassified
“…While the teaching reality is taken over by objective and subjective precariousness, it is to be expected that precariousness is extrapolated to the other dimensions of life, such as free time and leisure. Even before the covid-19 pandemic and the implementation of emergency remote teaching, Silvestre and Amaral (2019) already observed the scarce free time and elements of precariousness in the leisure of teachers in the São Paulo state network, with this precariousness being always greater among teachers with unstable work regimes. The fact is that long work hours and low wages have always constituted barriers to leisure experiences and practices among teachers in SEDUC-SP.…”
Section: Remote Teaching Work: Expopriation Of Lifementioning
confidence: 99%
“…The results revealed that Brazilian men enjoy more leisure hours than women; however, there has been a trend toward reducing this disparity over the years. Silvestre and Franco (2019) investigated the manifestations of the leisure phenomenon among teaching staff of the Sao Paulo State Department of Education. An analysis of documents revealed a link between teachers' leisure time and space and their work.…”
Section: Introductionmentioning
confidence: 99%